Transforming Ideas to Innovations: A Methodology for 3D Systems Development - Dreher, Carl; Reiners, Torsten; Dreher, Heinz (Springer, 2013)
We live in exciting and challenging times—the rapid pace of technological development is wind in the sails of social, commercial, and political change. When presented with changing circumstances, adaptation is important for individuals and organisations alike. For those engaging in the modern knowledge/networked economy, research, development, and commercialisation are important tools in facilitating innovation. Digital Ecosystems are an emergent player in the networked economy. Digital Ecosystems’ integration of technological empowerment and social networking gives them great potential for innovation. In particular, 3D Digital Ecosystems (3DDEs) are a rich forum for information systems research, development, and commercialisation because they provide a powerful context for innovation and collaboration through promoting user-generated content. For example, Second Life empowers users with a menu-based object-builder and a programming language. The immersive 3D environment provides in-built text, voice, and body-language communication tools that enrich collaboration. Furthermore, the community of users apply themselves to all realms of human endeavour, from recreational socialisation to systems development and entrepreneurial ventures.This chapter describes the benefits and limitations of using 3DDEs for research, development, and commercialisation. Based on our lessons learned from various university research projects (including discussion of a research commercialisation system development project of an Automated Essay Grading system called MarkIT), we introduce a new 3DDE system development methodology entitled MEADS—Methodology for Avatar-based Development of Systems. MEADS incorporates concepts and experience from different fields and establishes a guideline for 3DDE projects and covers the whole life cycle. In concluding This chapter, we make suggestions for future innovations in research, development, and commercialisation of Information Systems incorporating 3DDEs.